Kazakhstan context of Eurasian integration and the EEU in the critical field of Western experts (International relations and international law Journal, 2016)
The Eurasian Economic Union (EEU) began to operate in January 1, 2015. Kazakhstan is one of the main organizers of the new union. The EEU considered from the point of view «from the perspective of the relations of Kazakhstan with Russia and with the West» in the context of critical perception of Western experts. The article analyzes the range of opinions on the establishment and further operation of the EEU. There is certain recognition of the EEU as a «prepared union». Within the frameworks of the Customs Union «trade barriers were removed gradually, domestic markets got common external borders». Along with the positive tone regarding the economic nature of the new union, there is a pronounced critique of the «Eurasianism as an ideology», and of the «political pressure from Russia on the participants». Contradictions in the estimates the EEU and the ambiguity of perception do not mean that the Eurasian project has no prospects.
Keywords: Eurasian Economic Union (EEU); Eurasianism; Eurasian idea; integration; geopolitics; «Re-Sovietize»